Mortality and cancer incidence among workers in an abrasive manufacturing industry. Issue 1 (January 1987) - Edling, C; Järvholm, B; Andersson, L; Axelson, O
Abstract : Earlier epidemiological studies have shown that exposure to aluminium oxide and silicon carbide might carry with it an increased risk of lymphomas, stomach cancer, and non-malignant respiratory disease. To elucidate further this possible hazard, the cancer morbidity and the total mortality pattern was studied among 521 men manufacturing abrasive materials who had been exposed to aluminium oxide, silicon carbide, and formaldehyde. Total dust levels were in the range of 0.1-1.0 mg/m3. The cohort was followed up from 1958 until December 1983. No significant increase was found in total mortality, cancer mortality, or incidence of non-malignant respiratory diseases.